Алгоритм згущення дискретно представлених кривих на основі тотожностей із забезпеченням відсутності осциляції - Щербина, Віктор Михайлович; Щербина, Виктор Михайлович; Shcherbyna, Viktor; Пихтєєва, Ірина Вікторівна; Пыхтеева, Ирина Викторовна; Pykhtieieva, Iryna; Бондаренко, Лариса Юріївна; Бондаренко, Лариса Юрьевна; Bondarenko, Larysa (My University, 2019)
UK: Інтерполяція (згущення) дискретно представлених кривих (ДПК) надає можливість більш точного уяснення динаміки протекання того, чи іншого процесу, та пов’язана із визначенням оптимальних або необхідних результатів дослідженнь. Відомо, що одним, більш розвиненим, напрямком розвитку методів згущення дискретно представлених кривих (ДПК) є згущення на основі тотожностей. У даній роботі розглядається вплив формули згущення на основі базисного 3-полінома на різницеву схему, отриману на основі тотожностей згущення. Визначається, що властивість цього впливу використовується у алгоритмі методу згущення на основі тотожностей з урахуванням корекції в області розв’язку. Також, в роботі, визначається, що запропонована різницева схема дає можливість корекції розв’язку і отримання не осцилюючого однозначного ряду довільної конфігурації. RU: Интерполяция (сгущение) дискретно представленных кривых (ДПК) дает возможность более точного уяснения динамики протекания того или иного процесса и связана с определением оптимальных или необходимых результатов исследований. Известно, что одним, более развитым, направлением методики сгущения дискретно представленных кривых (ДПК) является сгущение на основе тождеств. В данной работе рассматривается влияние формулы сгущения на основе базисного 3-полинома на разностную схему, полученную на основе тождеств сгущения. Делается акцент на то, что свойство этого влияния используется в алгоритме метода сгущения на основе тождеств с учетом коррекции в области решения. Также, в работе, отмечено, что предложенная разностная схема дает возможность коррекции решения и получение неосциллирующего однозначного ряда произвольной конфигурации. EN: Interpolation (condensation) of discretely submitted curves (DSC) enables more exact explanation of dynamics of course of this or that process and is connected to definition of optimum or necessary results of researches. It is known, that to one, more advanced, a direction of a technique of a condensation of discretely submitted curves (DSC) is the condensation on the basis of identities. The method of condensation DSC on the basis of identities is used in many cases of the decision of the tasks connected to application of a technique of a condensation of experimentally received dot numbers{lines} as results of researches, and, in our opinion, is the most advanced method of interpolation. However, application of an offered method, does not allow to take into account all aspects, to the full. Proceeding from this, there is a necessity to consider other opportunities of a method of a condensation on the basis of identities. Proceeding from this there is a necessity of an establishment of connection a difference of the circuit received on the basis of identities of a condensation, with the formula of a condensation on the basis of a basic 3-polynom and revealing of properties of this onnection. In the given work influence of the formula of a condensation is considered on the basis of a basic 3-polynom on разностную the circuit received on the basis of identities of a condensation. That property of this influence is used in algorithm of a method of a condensation on the basis of identities in view of correction in the field of the decision emphasizes. Also, in work, it is marked, that suggested difference scheme the circuit enables correction of the decision and reception not oscillation unequivocal lines of an any configuration. Due to this it is possible to generate more flexible algorithm of a method of condensation DSC on the basis of identities.
Алгоритм сгущения дискретно представленых кривых на основе тождеств с обеспечением отсутствия осцилляции
Algorithm of a condensation of discretely submitted curves on the basis of identities with maintenance of absence oscillation
Keywords: 2-поліном; базисний 3-поліном; різницева схема; тотожність згущення; 2-полином; базисный 3-полином; разностная схема; тождество сгущения; 2-polynom; a basic 3-polynom; identity of a condensation; difference the circuit